Pengaruh Performance Expectancy, Effort Expectancy dan Social Influence terhadap Behavioral Intention dalam Implementasi Aplikasi SIMPG PT Perkebunan Nusantara XI Surabaya - Adelwin Hilman Wibowo; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sugar Factory Management Information System Application (SIMPG) is a monitoring application developed by PT. Perkebunan Nusantara XI which is used to monitor and supervise the growth of sugarcane in the rice fields. Problems arising from the use of the SIMPG information system application are some users of the SIMPG application who are less committed and inconsistent in using it thoroughly. In this study,the writer used 3 variables taken from the UTAUT model, namely Performance Expectancy, Effort Expectancy and Social Influence that affect user acceptance and user intentions in using the SIMPG (Behavioral Intention) application. This study aims to determine whether the three independent variables used have an influence on the dependent variable. The analytical method used is multiple linear regression analysis method. In this study the respondents who participated were employees of PT Perkebunan Nusantara XI Surabaya who used the SIMPG application which is spread in each sugar factory in East Java. The data collection, in this study, used a questionnaire and the number of samples obtained amounted to 71 people. The results obtained are the Effort Expectancy variable has a significant effect on the Behavioral Intention variable while the Performance Expectancy variable and the Social Influence variable have no significant effect on the Behavioral Intention variable.